In Vitro Antagonistic Effect of Lactic Acid Bacteria Isolated from Fermented Beverage and Finfish on Pathogenic and Foodborne Pathogenic Microorganism in Ethiopia - Fitsum Dejene; Belayneh Regasa Dadi; Dagimawie Tadesse (International Journal of Microbiology)
Background. Lactic acid bacteria from fermented foods and fish can antagonistically inhibit the growth of foodborne pathogenic organism in fermented food and they stimulate the immune response to protect the fish from certain kinds of infections. The aim of this study was to evaluate the in vitro antagonistic activities of lactic acid bacteria isolated from fermented beverage (Borde) and finfish on foodborne pathogenic microorganisms. Methods. Laboratory-based experimental study was conducted from May 1 to Sep 1, 2020. Total sample numbers were 60 samples of fermented beverage (Borde) and 20 of finfish which were collected from different households and Chamo Lake (Arba Minch, Ethiopia). Each sample was firstly homogenized and serial dilution was prepared and spread on MRS agar plates in order to isolate pure culture. Different biochemical tests were performed to identify isolated bacteria. Then, cell-free supernatant (CFS) was prepared from MRS culture and used in an antimicrobial assay that was performed by agar diffusion method. The effects of pH, temperature, and enzymes on antimicrobial activity were evaluated in the same test. Simultaneously, the effects of lactic acid bacteria on aflatoxin production and on the permeability of the membrane were also evaluated. Data were analyzed using one-way ANOVA and Tukey post hoc analysis was performed by SPSS 25 statistical software. Result. A total of 40 lactic acid bacteria were isolated; among them, 4 lactic acid bacteria, belonging to the genera Enterococcus, Leuconostoc, and Weisellia from fermented beverage and Pediococcus from fish, were screened for antimicrobial activity. The cell-free supernatant of those four isolates exhibited a significant (p<0.05) antibacterial effect against tested pathogens and foodborne pathogenic bacteria. In addition, CFS showed antifungal and antiaflatoxigenic activities. The antimicrobial compounds synthesized by these isolates were sensitive to some proteolytic enzymes, and they were proved to be stable at high temperatures. It maintained/retained antimicrobial activity in a wide range of pH 2.0–10. Enterococcal CFS exhibited antibacterial activity against S. aureus on membrane permeability, as confirmed by the increase in absorbance value between 0.075 and 0.24 at OD280-nm and between 0.68 and 1.2 at OD260-nm. Conclusion. Cell-free supernatant produced by isolated lactic acid bacteria showed antimicrobial activity against a wide range of Gram-positive and Gram-negative foodborne bacteria, suggesting its potential application as a natural antimicrobial agent in tackling the rising drug resistance against foodborne pathogens.